The Prosecutor : An Inquiry into the Exercise of Discretion - Grosman, Brian A. (Book collections on Project MUSE., 1978)
Every day decisions made by prosecutors, before trial takes place, critically affect the rights of citizens; yet these decisions remain a grey area in the administration of criminal justice. In fact, there are considerable and important differences between what the prosecutor does and what the legal literature and judicial decisions say he should do. Very little is known about the powers wielded by prosecutors and the factors which influence their exercise of discretion. This inquiry focuses on the decision-making role of the prosecutor in pre-trial determinations. Professor Grosman describes and analyses the prosecutor's informal relations with the police and defence lawyers, and the significance these relationships have for the accused and for the fair administration of justice. Other areas examined include the decision to begin prosecution, the negotiated guilty plea, and the prosecutor's administrative bias. The study concludes with recommendations for judicial and legislative reform. Professor Grosman has added a preface to this edition outlining the changes that have occurred in recent years. A lucid and revealing description of the prosecutor's attitudes to criminal prosecution and its operation, this study contributes important insights valuable to lawyers and all those concerned with the administration of justice, and will be of interest to everyone concerned with social problems.